The Rationale for Using Bacteriophage to Treat and Prevent Periprosthetic Joint Infections - Van Belleghem, Jonas D.; Manasherob, Robert; Miȩdzybrodzki, Ryszard; Rogóż, Paweł; Górski, Andrzej; Suh, Gina A.; Bollyky, Paul L.; Amanatullah, Derek F. (Frontiers in Microbiology, 2020)
Prosthetic joint infection (PJI) is a devastating complication after a joint replacement. PJI and its treatment have a high monetary cost, morbidity, and mortality. The lack of success treating PJI with conventional antibiotics alone is related to the presence of bacterial biofilm on medical implants. Consequently, surgical removal of the implant and prolonged intravenous antibiotics to eradicate the infection are necessary prior to re-implanting a new prosthetic joint. Growing clinical data shows that bacterial predators, called bacteriophages (phages), could be an alternative treatment strategy or prophylactic approach for PJI. Phages could further be exploited to degrade biofilms, making bacteria more susceptible to antibiotics and enabling potential combinatorial therapies. Emerging research suggests that phages may also directly interact with the innate immune response. Phage therapy may play an important, and currently understudied, role in the clearance of PJI, and has the potential to treat thousands of patients who would either have to undergo revision surgery to attempt to clear an infections, take antibiotics for a prolonged period to try and suppress the re-emerging infection, or potentially risk losing a limb.